Youth Participation in Volunteerism: The “Komunitas Milenial Bergerak” of Yogyakarta - Aufanda Raditya Nabil Al Manan; Halimatus Sa'diyah (UIN Siber Syekh Nurjati Cirebon, 2025)
Youth participation in volunteer activities is not always perceived positively, as young people are often considered to lack professional experience. The Milenial Bergerak Community in Yogyakarta serves as a platform for youth to engage in community-based volunteerism. This study aims to examine the factors that motivate youth participation in volunteer activities within the Milenial Bergerak Community. The research employed a qualitative approach using a case study method, involving nine informants consisting of board members and active volunteers from the first batch of the community. Data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that youth participation is driven by interrelated motivational factors based on functional motivation theory. The dominant motivation falls under the values category, reflecting altruistic intentions such as helping others, sharing happiness, and gaining inner satisfaction, followed by the understanding category, which emphasizes the desire to learn and expand social awareness. Other motivations identified include protective, enhancement, and career. The source of motivation is predominantly intrinsic, originating from internal personal values rather than external rewards. The dominance of intrinsic motivation suggests that the sustainability of youth volunteer movements is strongly influenced by personal meaning and social awareness, indicating the importance of strengthening reflective spaces and learning-oriented engagement within volunteer communities